Evaluasi Komputasi 1-phenyl-1H-benzimidazole (S5) sebagai Sensor Kolorimetri Ion Sianida Berbasis Ikatan Hidrogen - Rahmawati Rahmawati; Syarifa Wahidah Al Idrus (Lembaga Yasin AlSys, 2026)
Rapid detection of cyanide ions (CN⁻) with a WHO threshold of 1.9 × 10⁻⁶ M requires the development of an economical and selective colorimetric sensor. This study aims to evaluate 1-phenyl-1H-benzimidazole (S5) as a candidate CN⁻ sensor through a computational approach. This study used DFT/B3LYP/6-31G(d) and TD-DFT methods to analyze electronic properties, molecular interactions, UV-Vis spectral shifts, binding constants, detection limits, and electrostatic potential maps. The calculation results show that S5 has a HOMO energy of -5.5325 eV, a LUMO energy of -2.5569 eV, and an energy gap (ΔE) of 2.9757 eV. The interaction of S5 with CN⁻ formed the S5-CN complex through N-H···N≡C hydrogen bonding, which narrowed ΔE to 2.6578 eV or decreased it by 0.3179 eV. This narrowing of ΔE induced a bathochromic shift in the UV-Vis spectrum, which serves as the basis for color change. The binding constant k_bind value of 2.9 × 10³ M⁻¹ and detection limit of 4.36 × 10⁻⁴ M indicate that S5 has moderate affinity, but its sensitivity remains low. The ESP map confirms that N-H acts as the active site. The conclusion of this study affirms that although S5 is selective toward CN⁻, its detection limit remains 230 times above the WHO threshold, indicating that further structural modification is required. This study provides an initial contribution to establishing S5 as a basic framework for the design of next-generation benzimidazole-based cyanide sensors.